Efektivitas Penerapan Sanksi Hukum Terhadap Pelaku Tindak Pidana Pencabulan Anak Dibawah Umur ( Studi Kasus Perkara Nomor 90/Pid.Sus/2024/Pn.Kbr) - Donna Wijaya Putri; Sry Wahyuni (CV. ITTC INDONESIA, 2026)
Children are a gift from God Almighty as well as a trust that must be protected. Sexual violence against children is a serious crime that causes long-term psychological impacts. Children, as a vulnerable group, require special protection from both society and the state. The effectiveness of the law is measured by the extent to which law enforcement achieves the goal of child protection as stipulated in legislation. The case in focus is the criminal act of sexual abuse of a minor committed by Rangga Hadi Saputra in case Number 90/Pid.Sus/2024/PN Kbr. The public prosecutor demanded seven years of imprisonment, but the judge sentenced the defendant to five years in prison and a fine of IDR 10 million. The defendant’s actions violated Article 76D in conjunction with Article 81 paragraph (2) of Law No. 35 of 2014 on Child Protection (amendment to Law No. 23 of 2002) as amended by Law No. 17 of 2016. The formulated research problems are as follows, How effective is the application of legal sanctions against perpetrators of child molestation under the prevailing laws and regulations.What were the judge's considerations in imposing a criminal sentence on the perpetrator in Case Number 90/Pid.Sus/2024/PN Kbr, This research uses the normative juridical method, namely analyzing positive legal provisions and court decisions. Effective law enforcement requires key stages: professional and victim-sensitive investigation, a judicial process that ensures punishment proportional to the crime, and the execution of the sentence that provides a deterrent effect. Light sentences can reduce public trust in the legal system. In this decision, the judge considered the fulfillment of the elements of the criminal act in accordance with Article 76D in conjunction with Article 81 paragraph (2) of the Child Protection Law. Mitigating factors included the defendant’s cooperative attitude and confession of the crime. However, the author considers the five-year prison sentence insufficient to provide a maximum deterrent effect, given that the statutory penalty in the article is higher. Historically, the effectiveness of legal sanctions for child sexual abuse in Indonesia has developed alongside regulatory changes. The old Criminal Code was deemed ineffective due to light sanctions and narrow definitions. Law No. 39 of 1999 on Human Rights provided a philosophical basis for child protection. Law No. 23 of 2002, later amended by Law No. 35 of 2014, increased penalties and adopted a victim-centered approach. This development continued with the enactment of the Sexual Violence Crimes Law (Law on TPKS) in 2022 and the New Criminal Code in 2023. Although the normative framework has become more progressive, the effectiveness of child protection remains influenced by its implementation in practice. Strengthening the capacity of law enforcement officers and ensuring consistent application of sanctions are key to reducing the incidence of sexual violence against children.